2017
DOI: 10.18203/2319-2003.ijbcp20172044
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and antioxidant activity of Murraya Koenigii leaves extract against paracetamol induced hepatotoxicity in Rats

Abstract: Background: Many pharmacological substances are known to cause hepatic injuries and paracetamol is one out of them. This study was carried out to investigate the hepatoprotective and antioxidant activity of hydroalcoholic extract of Murraya koenigii leaves in paracetamol induced hepatotoxicity in Rats.Methods: Experimental animal used in this study were 30 healthy male albino Wistar rats of 10 to 12 wks weighing 180 ± 20 g. After acclimatization for a period of one week, the rats were randomized into five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Increased ALP synthesis in response to rising biliary pressure may be the cause of the elevated ALP serum level. [17][18][19][20] In the present study, a tested acute oral APAP dose is capable to elevate ALT, AST, and ALP activities in the blood (significant elevation) compared to the control animals group, which may be an indication of liver damage and cell necrosis resulting from the formation of NAPQI over GSH detoxification capacity. 17,19 A few earlier studies have shown the same findings.…”
Section: Discussionmentioning
confidence: 53%
“…Increased ALP synthesis in response to rising biliary pressure may be the cause of the elevated ALP serum level. [17][18][19][20] In the present study, a tested acute oral APAP dose is capable to elevate ALT, AST, and ALP activities in the blood (significant elevation) compared to the control animals group, which may be an indication of liver damage and cell necrosis resulting from the formation of NAPQI over GSH detoxification capacity. 17,19 A few earlier studies have shown the same findings.…”
Section: Discussionmentioning
confidence: 53%
“…Alkaloids are the majority of compounds that presences in this sample. Leaves of M. koenigii contained alkaloids and tannins (Salwe et al, 2017), alkaloids, terpenoids and flavonoids (Patil, 2018), alkaloids, saponins, tannins, andflavonoids (Widyanti et al, 2019), alkaloids and terpenoids (Mustanir et al, 2019), alkaloids (Samantha el al., 2018 and terpenoids and polyphenols (Tan et al, 2017)…”
Section: Results and Discussion Separation Compound Using Column Chromatographymentioning
confidence: 99%
“…The decreased lethality effect of the extracts observed in the present study led to subsequent investigations carried out to confirm further hepatoprotective effects. The optimum dose of APAP (2 g/kg), which induced the liver damage, was determined to be 2 g/kg through the selection of three doses from previous studies, which was a similar procedure used in other studies [ 28 , 39 ]. In the present study, administration of 2 g/kg APAP resulted in significant elevation of serum levels ALT, AST, ALP, TB, lipid profiles, LDL, TC, and TGs and decreased serum level of HDL, which was in agreement with the previous study [ 40 ].…”
Section: Discussionmentioning
confidence: 99%